The commitment role of equity financing - Matthias Fahn; Georg Wamser; Valeria Merlo (Johannes Kepler University of Linz, Department of Economics, 2017)
Existing theories of a firm's optimal capital structure seem to fail in explaining why many healthy and profitable firms rely heavily on equity financing, even though benefits associated with debt (like tax shields) appear to be high and the bankruptcy risk low. This holds in particular for firms that show a strong commitment towards their workforce and are popular among employees. We demonstrate that such financing behavior may be driven by implicit arrangements made between a firm and its managers/employees. Equity financing generally strengthens a firm's credibility to honor implicit promises. Debt, however, has an adverse effect on the enforceability of these arrangements because too much debt increases the firm's reneging temptation, as some of the negative consequences of breaking implicit promises can be shifted to creditors. Our analysis provides an explanation for why some firms only use little debt financing. Predictions made by our theory are in line with a number of empirical results, which seem to stay in contrast to existing theories on capital structure.
Keywords: C73; D24; D86; G32; 330; relational contracts; capital structure; corporate finance; debt financing